Activitatea pedagogică şi ştiinţifică a lui A. Ghebos ca profesor la catedra de psihologie a Universităţii “A. Russo” din Bălţi [Articol] - Carazanu, Vasile (USARB, 2011)
The given article is dedicated to A. Ghebos, contribution a distinguished scientist, Ph.D. in psychology, and his to the development of the psychological science from the R. of M, and those works, articles, collections which include suggestions for school teachers with the aim of young generation s training process improvement. Also it describes the colloquium of homage dedicated to A.Ghebos that took place at the faculty of Pedagogy and Psychology with the participation of university lecturers and students from the above mentioned faculty.
Keywords: Ghebos Anatolie (1938-1992); psiholog; Bălţi